PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERHITUNG AWAL ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK SABBIHISMA 4 PADANG - Lola Anjela; Serli Marlina; Setiyo Utoyo; Zulminiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to investigate the influence of the Project Based Learning model on the early numeracy skills of children aged 5–6 years at Sabbihisma 4 Kindergarten, Padang. Preliminary observations indicated that the children’s numeracy abilities were still underdeveloped, as shown by the difficulty some experienced in counting, sequencing, and writing numbers from 1 to 20. Adopting a quantitative approach, the research applied an experimental design in the form of a Quasi-Experiment. The study population included all children enrolled at Sabbihisma 4 Kindergarten, with the sample comprising 10 children each from classes B5 and B6. Data were obtained through testing and analyzed using normality, homogeneity, and hypothesis tests. Results revealed that in the experimental group, the mean pre-test score of 9.9 rose to 20.6 in the post-test, with a Sig. (2-tailed) value of 0.002, which is below the threshold of 0.05. These findings suggest that the use of the Project Based Learning model significantly improved early numeracy skills at Sabbihisma 4 Kindergarten, Padang.